2012
DOI: 10.1177/193229681200600629
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Glucose Monitoring in Pregnancy: New Frontiers in Clinical Applications and Research

Abstract: Abbreviations: (AUC) area under the curve, (CGM) continuous glucose monitoring, (CSII) continuous subcutaneous insulin infusion, (GDM) gestational diabetes mellitus, (HbA1c) hemoglobin A1c, (MAD) mean absolute difference, (MARD) mean absolute relative difference, (SMBG) self-monitoring of blood glucose, (T1DM) type 1 diabetes mellitus, (T2DM) type 2 diabetes mellitus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…It has been shown that continuous glucose monitoring (CGM) is useful for evaluating glycemic control during pregnancy [14]. In the present study, we determined the mean blood glucose (MBG) by conducting CGM in pregnant women with diabetes to examine whether HbA1c and GA show a close correlation with MBG or not.…”
Section: Introductionmentioning
confidence: 97%
“…It has been shown that continuous glucose monitoring (CGM) is useful for evaluating glycemic control during pregnancy [14]. In the present study, we determined the mean blood glucose (MBG) by conducting CGM in pregnant women with diabetes to examine whether HbA1c and GA show a close correlation with MBG or not.…”
Section: Introductionmentioning
confidence: 97%
“…Second, we estimated HbA1c and GA using MBG obtained from the diurnal variation, not by continuous glucose monitoring (CGM), which is more accurate for evaluating glycaemic control. 28 Third, the adjGA has not been generalized in this population. Fourth, we did not show any reliable data of long-term glycaemic control except for HbA1c or GA. Further, the GA/HbA1c ratio might show the significant diversity in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“… 5–11 Continuous glucose monitoring (CGM) systems measure interstitial glucose levels by implanting a sensor subcutaneously. 12 Typically, finger prick blood glucose measurements are needed to calibrate the interstitial glucose levels to capillary blood glucose levels, although devices that do not need this calibration step are now becoming increasingly available. 12 , 13 Throughout this paper we refer to the sensor predicted capillary glucose levels as ‘sensor glucose’.…”
Section: Introductionmentioning
confidence: 99%